2020
DOI: 10.3390/molecules25235769
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Natural Products

Abstract: Natural products and their biological activities are currently a subject of great interest in the pharmaceutical, health food, and cosmetics industries, and numbers of scientific studies in this field are increasing rapidly [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…Natural products refer to a wide range of bioactive extracts or isolated metabolites from natural materials. Their bioactivities are currently of great interest in many research fields (Ekiert and Szopa, 2020) and may yield promising pharmacological approaches for the prevention and treatment of UC due to their multiple regulatory effects with few adverse effects (Nascimento et al, 2020). In recent years, converging lines of evidence have demonstrated that apoptosis of IECs is highly associated with the occurrence and development of UC.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products refer to a wide range of bioactive extracts or isolated metabolites from natural materials. Their bioactivities are currently of great interest in many research fields (Ekiert and Szopa, 2020) and may yield promising pharmacological approaches for the prevention and treatment of UC due to their multiple regulatory effects with few adverse effects (Nascimento et al, 2020). In recent years, converging lines of evidence have demonstrated that apoptosis of IECs is highly associated with the occurrence and development of UC.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products represent an important source of compounds used in the discovery of new therapeutic agents ( Harvey et al, 2015 ), which have relatively single compounds with good drug characteristics, including structural diversity and complexity, high selectivity and specific pharmacological activities, as well as novel therapeutic effects and mechanisms of action ( Barnett and Stallforth, 2018 ; Ekiert and Szopa, 2020 ). The importance of natural products in the prevention and treatment of heart disease is universally known.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products are bioactive components from natural organisms, including plants, animals, insects, marine organisms, microorganisms ( Xie et al, 2021 ). These agents have been widely used by human societies for thousands of years ( Baker et al, 2007 ), and their bioactivities are of great interest to enormous research fields ( Ekiert and Szopa, 2020 ). In recent decades, a growing body of research has demonstrated that natural products exert anti-apoptotic effects on METH-induced neurotoxicity and may yield promising targets for further investigation of effective pharmacological interventions.…”
Section: Introductionmentioning
confidence: 99%